Effectiveness of EU regional policy: Evidence from a natural experiment in Finland - Ville Vehkasalo (REGION, 2018)
European Union regional policy is implemented through structural funds, such as the European Regional Development Fund (ERDF), which support investment in peripheral regions of the EU. We studied the effects of EU regional policy on key economic variables using a rare natural experiment setting. In 2007, parts of regions that were previously covered by the ERDF programme for Western Finland were reallocated to the ERDF programme for Northern Finland, with higher support intensity per capita. This area reallocation was caused by the newly adopted EU legislation regulating the classification of regional statistical areas. With a detailed postal code area dataset and a difference-in-differences estimator, we discovered desirable regional policy effects on unemployment and the number of jobs.
Keywords: 330; Microeconometrics; Policy analysis; Regional policy